Impact of Pathologic Complete Response following Neoadjuvant Chemotherapy ± Trastuzumab in Locally Advanced Breast Cancer. (12th February 2021) - Al-Tweigeri, Taher; Elshenawy, Mahmoud; Badran, Ahmed; Omar, Ayman; Suleman, Kausar; Al Malik, Osama; Anwar, Ihab; Jastaniya, Noha; Tulbah, Asma; Al Shabanah, Mohammad; Ajarim, Dahish; Al Sayed, Adher
Abstract : Purpose . This study was designed to examine the relationship between breast cancer molecular subtypes and pathological response to neoadjuvant chemotherapy (NAC) ± trastuzumab, in locally advanced breast cancer (LABC). Methods . Female patients with LABC (T2–T4, N0–N2, and M0) who received neoadjuvant chemotherapy + trastuzumab if HER2+ subtype, followed by surgery and radiotherapy ± hormonal therapy, were identified. The primary endpoint was pathologic complete response (pCR) in the breast and axilla (ypT0/ypN0), with final analysis on disease-free survival (DFS) and overall survival (OS). Results . Six hundred eighty-one patients with a median age of 44 years, premenopausal: 70%, median tumour size: 7.0 cm (range 4–11 cm), stage II B: 27% and III A/III B: 73%, ER+/HER2−: 40.8%, ER−/HER2−: 23%, ER+/HER2+: 17.7%, and ER−/HER2+: 18.5%. Overall pCR (ypT0/ypN0) was 23%. The pCR rates based on molecular subtypes were ER+/HER2−: 9%; ER+/HER2+: 29%; ER−/HER2−: 31%; and ER−/HER2+: 37%. At median follow-up of 61 months, ER+/HER2+ and ER+/HER2− subtypes had the best 5-year DFS and OS; meanwhile, ER−/HER2+ and ER−/HER2− subtypes had the worst. Conclusion . Women with ER+/HER2− disease are the least likely to achieve pCR, with the highest rates in HER2+ and triple-negative subgroups. Degree of response is associated with OS; despite the comparatively higher likelihood of achieving pCR in ER−/HER2+ and triple-negative, these subgroups experience a survival detriment. We are consistent with the published data that patients who attain the pathological complete response defined as ypT0/ypN0 have improved outcomes.